Preventive Against Fraud: A Case Study of Independent Village Performance in Bone District, Indonesia - Halimah Bachtiar, Irmah; Zulfaidah; Supiati (International Journal of Accounting and Economics Studies, 2026)
Corruption is still one of the problems that is difficult to solve in Indonesia. The purpose of this study was to determine the impact of Islamic corporate governance variables, internal control systems, whistleblowing, and community empowerment on efforts to prevent Fraud in the distribution of village fundsin independent villages, Bone Regency. The sample was selected based on accidental sampling techniques by distributing questionnaires to 202 samples consisting of village officials and communities in 82 independent villages in Bone Regency, South Sulawesi, Indonesia. The use of data analysis methods in this study involved descriptive tests using the Validity and Reliability test. The measurement of the questionnaire was based on a Likert scale and data analysis techniques through Structural Equation Models using SMART-PLS tools. The results of the study indicate that Islamic corporate governance, internal control systems, and community empowerment have a positive and significant effect on efforts to prevent fraud, and whistleblowing influences preventing fraud in independent villages. These results contribute to the importance of implementing Islamic governance where most of the village population is Muslim and improving the internal control system and community involvement in the use of village funds so that fraud does not occur.
Keywords: Islamic Corporate Governance; Internal Control System; Whistleblowing; Community Empowerment; Fraud Distribution